RANTAI DIGITAL, KEUNTUNGAN OPERASIONAL: Tinjauan Sistematis tentang Tantangan Digitalisasi Rantai Pasokan dan Implikasi Efisiensi Operasional - Munawaroh, Munawaroh; Afifi, Muhammad Rahman; Abidin, Jaja Zaenal; Sujayanti, Susi (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
Digital transformation is fundamentally reshaping supply chain management, promising increased operational efficiency while also presenting implementation challenges that organizations must strategically address. This systematic literature review synthesizes empirical evidence examining the impact of supply chain digitalization on operational efficiency and identifies critical implementation barriers. Following an established review protocol, a comprehensive search across academic databases yielded 24 peer-reviewed publications (2019-2025) that were thematically analyzed. Findings indicate that digitalization technologies including the Internet of Things, artificial intelligence, enterprise resource planning systems, and big data analytics significantly improve operational efficiency through process automation, real-time visibility, predictive analytics, and enhanced stakeholder collaboration. However, organizations face significant challenges, including significant infrastructure investments, workforce capability gaps, vendor dependency risks, data security concerns, scalability complexities, and integration difficulties. The thematic synthesis identified six key challenge categories requiring proactive mitigation strategies. This research provides a systematic evidence synthesis that advances the understanding of supply chain digitalization while providing practical guidance for successful implementation. Organizations must conduct a comprehensive readiness assessment, develop a phased implementation roadmap, invest in workforce development, build a robust cybersecurity framework, and design a flexible and scalable architecture to maximize the benefits of digitalization while minimizing risks. Limitations of this study include the literature review methodology and temporal scope, which indicate the need for longitudinal empirical investigations to more deeply understand implementation dynamics.